Implementasi Kepala Sekolah Dalam Meningkatkan Kualitas SDM - Tengku Darmansah; Nazwa Alisya Harahap; Hulga Ryan Shori Sihombing; Yudha Pratama Nasution (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
The aim of this research is to determine the role of school principals in efforts to improve the quality of human resources. The principal is the most responsible and important component for the success of education in his school and for improving the quality of education. The role of the school principal in improving the quality of human resources includes being an Educator, Manager, Advisor, Supervisor, Leader, Innovator and Motivator (EMASLIM) in the educational institution he leads. The leadership success of a school principal is primarily based on his ability to lead effectively, which includes skills for managing human resources, making strategic decisions, and creating a harmonious school environment. The main key to ensuring the school principal's work runs smoothly lies in his ability to maintain emotional stability, face various challenges calmly, and maintain self-confidence in every situation.